2021
DOI: 10.3926/jairm.186
|View full text |Cite
|
Sign up to set email alerts
|

Applying airport centrality as an operational continuity indicator

Abstract: The research aims to propose a methodology to estimate the reliability of the Brazilian airport network (domestic passenger traffic), based on the centrality of airports (Network Theory). The applied methodologies are related to Network Theory, a branch of Graph Theory, and reliability. Reliability is associated with the good functioning of a product or system, the absence of breaks or failures in each period and the environmental conditions of use of the item. The data used refer to the period 2000-2018 and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This could be attributed to the anomalous centralities actually, which misestimate the role of nodes. Our work has the directed significance to the researches of measuring the influence of nodes [ 30 , 31 ], evaluating the robustness [ 43 , 50 , 53 ] and modeling the dynamical process [ 54 ] with the eigenvector centrality. In addition, other real networks embedded in two-dimensional space (such as bus networks [ 29 , 55 ], railway networks [ 56 ], power grid networks [ 57 ]) might also have similar behaviors of eigenvector centralities, empirical investigations on them would generalize our conclusions to other real systems.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to the anomalous centralities actually, which misestimate the role of nodes. Our work has the directed significance to the researches of measuring the influence of nodes [ 30 , 31 ], evaluating the robustness [ 43 , 50 , 53 ] and modeling the dynamical process [ 54 ] with the eigenvector centrality. In addition, other real networks embedded in two-dimensional space (such as bus networks [ 29 , 55 ], railway networks [ 56 ], power grid networks [ 57 ]) might also have similar behaviors of eigenvector centralities, empirical investigations on them would generalize our conclusions to other real systems.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Commonly, an airport with a large value of eigenvector centrality either has many relatively unimportant neighbors or has several important ones. Brito et al [ 30 ] found that the larger the value of a node in Brazilian airport networks, the higher the probability of an airport’s operating regularly. Clark et al [ 31 ] noticed that in the unweighted American airport networks the degrees and the eigenvector centralities for most airports have a positive cross-relation.…”
Section: Introductionmentioning
confidence: 99%
“…Rocha (2009) examined the Brazilian airport network and captured the dynamic evolution of the system between 1995 and 2006 based on routes, connections, passengers, and cargo levels. In another study on Brazilian airports, Brito, Baltazar and Silva (2021) assessed the reliability of the Brazilian airport system using network theory as well. The US domestic air transport system was also analyzed, and the various network characteristics, such as shortest path, centrality, clustering, and resiliency, were examined (Xu & Harriss, 2008;Cheung & Gunes, 2012;Jia, Qin & Shan, 2014;Lin & Ban, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%